Being There? The Role of Journalistic Legwork Across New and Traditional Media. (December 2017) - Reich, Zvi; Godler, Yigal
In the age of spirited debates about the mediating role of technologies, the other side of the coin is the state of direct experience in contemporary news production, that is, cases in which news reporters still rely on traditional channels such as "legwork, " "firsthand witnessing, " or "shoe-leather reporting." The present study is a systematic attempt to identify journalists' reasons for engaging in legwork, by recreating item by item the work processes and reasoning behind hundreds of individual news reports produced in the digital age, across Israeli print, television, radio, and online news outlets ( N = 859). Insofar as legwork can serve as a proxy for painstaking journalism, journalists' decisions make some difference in determining if more or less legwork will ensue. The data avail an opportunity to explore scholarly musings about journalists' motivations behind legwork: be they knowledge related, medium related, or event related. We find support for all three possibilities and discuss the implications of these findings.